Male Concepts of Women in "Ligeia," "Berenice," and "The Fall of the House of Usher" by Edgar Allan Poe - Hagkvist, Annika (My University, 2002)
In this study I have analyzed the nineteenth-century dichotomy between the angel-woman and the monster-woman in Edgar Allan Poe's short stories "Berenice," "Ligeia," and "The Fall of the House of Usher." The analysis suggested that the angelic woman trapped in patriarchal confinement is inevitably bound to use her evil antithesis in order to counteract the threat posed by male domination, consequently reversing her oppression. Furthermore, the male character is oppressed by his own male image which is formed by patriarchal masculinity. Theoretically this study is mainly based on Sandra Gilbert and Susan Gubar's concept of the male-defined images imposed on women. The results of the analysis appeared to support the claim: the binary image is necessary for the female character to reverse the oppression and ultimately destroy the man who cannot escape from the woman's confinement he has himself created. The male character fails in upholding his masculine image, which further intensifies his own oppression.
Keywords: Edgar Allan Poe; gothic; feminism; masculinities; fi=Englannin kieli|en=English language|